Assessment of Radioactivity in Various Types of Soil From Al-Obour City, Egypt. - Ragab, Fatma (JOURNAL OF ADVANCES IN PHYSICS, 2018)
The distributions of natural radioactivity in various types of samples collected from several areas in Al-Obour city were determined using a high purity germanium (HPGe) detector. Four types of samples were investigated: soil, foundations, sand dunes and rock samples. The specific activities of 238U, 226Ra series, 232Th and 40K in soil; foundations; sand dunes and rock samples have a mean of (13.31±3.59); (12.96±3.63); (13.36±4.32) and (26.74±5.50), (6.49±0.23); (3.71±0.16); (3.87±0.17) and (19.38±0.64), (6.52±0.55); (4.03±0.46); (3.90±0.45) and (25.91±1.89) and (96.21±1.60); (78.12±1.46); (76.27±1.43) and (215.71±3.35)Bq/kg, respectively.It was also noticed that 137Cs is existed in some samples but is close to the background level. The hazard indices were also determined in all types of samples of the under study area. These values are important to establish baseline levels of this environmental radioactivity to detect any upcoming change for the local population.